Effects of Curcumin and Fenugreek Soluble Fiber on the Physical Working Capacity at the Fatigue Threshold, Peak Oxygen Consumption, and Time to Exhaustion. Issue 12 (December 2020) - Herrick, Lauren P.; Goh, Jensen; Menke, Walter; Campbell, Marilyn S.; Fleenor, Bradley S.; Abel, Mark G.; Bergstrom, Haley C.
Abstract : Abstract: Herrick, LP, Goh, J, Menke, W, Campbell, MS, Fleenor, BS, Abel, MG, and Bergstrom, HC. Effects of curcumin and fenugreek soluble fiber on the physical working capacity at the fatigue threshold, peak oxygen consumption, and time to exhaustion. J Strength Cond Res 34(12): 3346–3355, 2020—The purpose of this study was to examine the effects of curcumin in combination with fenugreek soluble fiber (CUR + FEN) or fenugreek soluble fiber alone (FEN) on the neuromuscular fatigue threshold (PWCFT ), peak oxygen consumption (V˙o2 peak), and time to exhaustion (Tlim ) on a graded exercise test (GXT), in untrained subjects. The PWCFT estimates the highest power output that can be maintained without evidence of neuromuscular fatigue. Forty-seven untrained, college-aged subjects were randomly assigned to one of 3 supplementation groups; placebo (PLA, n = 15), CUR + FEN (500 mg·d −1, n = 18), or FEN (300 mg·d −1, n = 14). The subjects completed a maximal GXT on a cycle ergometer to determine the PWCFT, V˙o2 peak, and Tlim before (PRE) and after (POST) 28 days of daily supplementation. Surface electromyographic signals were recorded from a bipolar electrode arrangement on the vastus lateralis of the right leg during each test. Separate one-way analysis of covariances were used to determine if there were between-group differences for adjusted POST-PWCFT, POST-V˙o2 peak, and POST-Tlim values, covaried for the respective PRE-test scores. The adjusted POST-PWCFT for the CUR + FEN group (mean ± SD : 196 ± 58 W) was greater ( p = 0.016) than the PLA group (168 ± 49 W) but the FEN group (185 ± 32 W) was not different from the CUR + FEN or PLA groups ( p > 0.05). There were no differences for adjusted POST-V˙o2 peak ( p = 0.612) or POST-Tlim ( p = 0.508) among the groups. These findings suggested curcumin combined with fenugreek soluble fiber might delay neuromuscular fatigue.